2014
DOI: 10.1515/hf-2014-0103
|View full text |Cite
|
Sign up to set email alerts
|

Urea-formaldehyde resin penetration into Pinus radiata tracheid walls assessed by TEM-EDXS

Abstract: This paper reports a new method of detecting urea-formaldehyde (UF) resin penetration into the cell walls of radiata pine (Pinus radiata D. Don) by means of transmission electron microscopy (TEM) in combination with energy-dispersive X-ray spectroscopy (EDXS). The quantifications of penetrated UF resin in the ultrathin cuts of cell walls were realized by detecting nitrogen (N) element by TEM-EDXS. Both line scan and area mapping revealed N in cell walls in contact with resin-filled lumens but not in those in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This means that UF resins could penetrate through the cell wall. It proved that the TEM-EDS technique could be applied to analyze the UF resin penetration (Singh et al 2015). Interaction of UF resins with the cell walls comprises of physical and chemical reactions.…”
Section: Acid Buffering Capacity = (V1 X N Of Base X V2 X 100)/(v3 X W) (Meq/100g Od Fiber)mentioning
confidence: 98%
See 2 more Smart Citations
“…This means that UF resins could penetrate through the cell wall. It proved that the TEM-EDS technique could be applied to analyze the UF resin penetration (Singh et al 2015). Interaction of UF resins with the cell walls comprises of physical and chemical reactions.…”
Section: Acid Buffering Capacity = (V1 X N Of Base X V2 X 100)/(v3 X W) (Meq/100g Od Fiber)mentioning
confidence: 98%
“…Penetration of UF resins into radiata pine (Pinus radiata) tracheid walls was assessed using Transmission Electron Microscopy (TEM) combined with an Energy Dispersive X-ray Spectroscopy (EDS). Singh et al (2015) revealed that the lumen and cell walls were filled with N originated from UF resins. This means that UF resins could penetrate through the cell wall.…”
Section: Acid Buffering Capacity = (V1 X N Of Base X V2 X 100)/(v3 X W) (Meq/100g Od Fiber)mentioning
confidence: 99%
See 1 more Smart Citation
“…Confocal laser scanning microscopy (CLSM), using a laser scanning device on the basis of FM, can improve the spatial imaging resolution significantly, and even the adhesive diffused in the cell walls can be detected (Gavrilović-Grmuša et al 2012a,b). In addition to these optical microscopy techniques, electron microscopic methods such as X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), or transmission electron microscopy (TEM) in combination with energy dispersive X-ray spectroscopy (EDX) have also been employed to determine the amount of UF in wood semiquantitatively by detecting its chemical composition (Bolton et al 1988;Pakdel et al 2008;Singh et al 2015). Nanoindentation (NI), an important method for measuring the micromechanical properties of materials, has been used to determine the penetration behavior of adhesives indirectly by measuring the mechanical properties of cell walls in the interphase region (Liang et al 2011;Zhang et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the hydrolysis of cured UF resin adhesives in the wood-based composite panel seems unavoidable due to wood substance in a hygroscopic material. Further, as a binder, UF resin adhesives penetrated not only in cell lumens but also into tracheid walls [5]; thus interaction between wood and UF adhesives occurs continuously. Many studies have investigated the hydrolysis of UF resin adhesives to understand the mechanism of formaldehyde release, not only from pure cured UF resin adhesives [2,[6][7][8][9][10][11][12] but also from UF resin adhesive-bonded wood panel products [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%